The ecology and biology of Nephrops norvegicus - Johnson, Magnus L.; Johnson, Mark P. (Advances in marine biology, 2013)
Advances in Marine Biology has been providing in-depth and up-to-date reviews on all aspects of marine biology since 1963 -- over 40 years of outstanding coverage! The series is well-known for both its excellence of reviews and editing. Now edited by Michael Lesser (University of New Hampshire, USA), with an internationally renowned Editorial Board, the serial publishes in-depth and up-to-date content on a wide range of topics that will appeal to postgraduates and researchers in marine biology, fisheries science, ecology, zoology, and biological oceanography Advances in Marine Biology has been providing in-depth and up-to-date reviews on all aspects of marine biology since 1963. The series is well-known for both its excellence of reviews and editing.